Angels in John Chrysostom’s Anthropology: Asceticism, Angelomorphism, and Human Bodily Composition in Flux - De Wet, Chris L. (Journal of early Christian history, 2020)
The purpose of this article is to investigate the role of angels in John Chrysostom’s (c. 349–407 CE) anthropology. The article provides a short overview of Chrysostom’s thought regarding angels more generally. The focus here is especially on the origins, nature, and function of angels. Thereafter, the focus moves to Chrysostom’s “thinking with angels” in his anthropology. This section extrapolates the differences and similarities between humans and angels. The important question to which the analysis leads is that of angelomorphism, or becoming like the angels. Chrysostom often states that persons adopting ascetic and sacerdotal practices have the ability to become like the angels. In Chrysostom, angelology is especially an ascetic discourse. What does this statement mean for Chrysostom? What does angelomorphism entail in the anthropological sense? The study argues that priests, monks, and virgins are able to become like angels both in a functional and even in a limited essential sense.